Genomic Analysis of Molecular Bacterial Mechanisms of Resistance to Phage Infection - Ambroa, Antón; Blasco, Lucia; López, María; Pacios, Olga; Bleriot, Inés; Fernández-García, Laura; González de Aledo, Manuel; Ortiz-Cartagena, Concha; Millard, Andrew; Tomás, María (Frontiers in Microbiology, 2022)
In order to optimize phage therapy, we need to understand how bacteria evolve against phage attack. One of the main problems of the phage therapy is the appearance of bacterial resistance variants. The use of genomics to track antimicrobial resistance is increasingly developed and used in clinical laboratories. For that reason, it is important to consider, in an emerging future with phage therapy, to detect and avoid phage resistant strains, that can be overcome by the analysis of metadata provided by Whole Generation Sequencing (WGS). Here, we identified genes associated with phage resistance in 18 Acinetobacter baumannii clinical strain belonging to the ST-2 clonal complex during a decade (Ab2000 vs 2010): 9 from 2000 and 9 from 2010. The presence of genes putatively associated to phage resistance were detected. Genes detected were associated with an abortive infection system, restriction-modification system, genes predicted to be associated with defense systems but with unknown function and CRISPR-Cas system. Between 118 and 171 genes were found in the 18 clinical strains. On average, 26% of these genes were detected inside genomic islands (GIs) in the 2000 strains and 32% in 2010 strains. Furthermore, 38 potential CRISPR arrays in 17 of 18 of the strains were found, as well as 705 proteins associated with CRISPR-Cas systems. A moderately higher presence of these genes in the strains of the 2010 in comparison to those of the 2000 were found, especially those related to the R-M system and CRISPR-Cas system. The presence of these genes in GIs in a higher rate in the strains of the 2010 compared to those of the 2000 was also detected. WGS and bioinformatics could be powerful tools to avoid drawbacks when a personalized therapy is applied. In this study, it allows us to take care of the phage resistance in A. baumannii clinical strains to prevent a failure in a possible phage therapy.